Greening airports: A methodological framework for site assessment and assessing solar PV potential - Sreenath, S.; Sudhakar, K.; Ahmad Fitri, Yusop (Elsevier B.V., 2024)
Due to energy intensiveness and carbon emissions, the aviation sector is under continuous environmental pressure. In this regard, airports have shown keen interest in solar photovoltaic (PV) technology to decarbonize their energy consumption. Implementing onsite solar projects in the airport is challenging due to various technical and safety aspects. Improper siting of solar PV arrays may adversely affect the safety of the passengers. This paper aims to develop a methodological framework for site assessment and potential estimation of PV projects in airport locations. The developed methodology is applied as a case study to seven Indian airports: Madurai, Goa, Raipur, Ahmedabad, Lucknow, Amritsar, and Dehradun. It was understood that the suitable area for solar PV projects on airport land depends on airspace restrictions, built area, and glare occurrence. On average, 30–40 % of the airport land is observed to be built area; hence, it is unavailable for land-based solar PV systems. Among the studied airports, the highest value of technical potential is observed for Raipur airport (21 MW). These conservative estimates provide baseline information for airport planning and development projects. This study is expected to be a reference material for energy specialists, airport stakeholders, and policymakers.